2017
DOI: 10.1016/j.actbio.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Osteoinductive recombinant silk fusion proteins for bone regeneration

Abstract: Protein polymers provide a unique opportunity for tunable designs of material systems due to the genetic basis of sequence control. To address the challenge of biomineralization interfaces with protein based materials, we genetically engineered spider silks to design organic-inorganic hybrid systems. The spider silk inspired domain (SGRGGLGGQG AGAAAAAGGA GQGGYGGLGSQGT)15 served as an organic scaffold to control material stability and to allow multiple modes of processing, whereas the hydroxyapatite binding dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 39 publications
0
69
0
Order By: Relevance
“…Films made of this fusion protein not only induced the deposition of CaP, but also allowed good adhesion of human mesenchymal stem cells and significant improvement of their differentiation. To address the enhancement of biomineralization of the interface of protein-based biomaterials and tissues, the same research group reported the production of silk-hybrids with silica binding peptides [75], as well as genetically engineered spider silk proteins (silk-VTKHLNQISQSY (VTK) fusion proteins) with specific domains (SGRGGLGGQG AGAAAAAGGA GQGGYGGLGSQGT)15 and films made thereof [76]. Plowright et al [75] showed that fusion of spider silk with silica-binding peptide R5 (SSKKSGSYSGSKGSKRRIL), taken from silaffin of Cerithiopsis fusiformis, at both termini of the silk…”
Section: Bone and Cartilage Tissue Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Films made of this fusion protein not only induced the deposition of CaP, but also allowed good adhesion of human mesenchymal stem cells and significant improvement of their differentiation. To address the enhancement of biomineralization of the interface of protein-based biomaterials and tissues, the same research group reported the production of silk-hybrids with silica binding peptides [75], as well as genetically engineered spider silk proteins (silk-VTKHLNQISQSY (VTK) fusion proteins) with specific domains (SGRGGLGGQG AGAAAAAGGA GQGGYGGLGSQGT)15 and films made thereof [76]. Plowright et al [75] showed that fusion of spider silk with silica-binding peptide R5 (SSKKSGSYSGSKGSKRRIL), taken from silaffin of Cerithiopsis fusiformis, at both termini of the silk…”
Section: Bone and Cartilage Tissue Regenerationmentioning
confidence: 99%
“…They used a major ampullate spidroin (MaSp1) of Nephila clavipes functionalized with bone sialoprotein (BSP) fusion protein to induce cell attachment, differentiation and deposition of calcium phosphate on the surface of a film yielding an accelerated calcification in vitro after 6 h at 37 • C. Films made of this fusion protein not only induced the deposition of CaP, but also allowed good adhesion of human mesenchymal stem cells and significant improvement of their differentiation. To address the enhancement of biomineralization of the interface of protein-based biomaterials and tissues, the same research group reported the production of silk-hybrids with silica binding peptides [75], as well as genetically engineered spider silk proteins (silk-VTKHLNQISQSY (VTK) fusion proteins) with specific domains (SGRGGLGGQG AGAAAAAGGA GQGGYGGLGSQGT) 15 and films made thereof [76]. Plowright et al [75] showed that fusion of spider silk with silica-binding peptide R5 (SSKKSGSYSGSKGSKRRIL), taken from silaffin of Cerithiopsis fusiformis, at both termini of the silk sequence (SGRGGLGGQGAGAAAAAGGAGQGGYGGLGSQGT) 15 , derived from the consensus repeat of Nephila clavipes MaSp1, induced biosilicification.…”
Section: Bone and Cartilage Tissue Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported the development of a library of SELP proteins by modification of the elastin sequence to generate SELPs with stimuli-responsive properties to pH, redox, temperature, electric field, and ionic strength, and utilized functional materials screening to isolate useful sequences from the library for further materials characterization [35]. The block copolymer structure of SELPs provides an additional design feature that enables future combinations of sequences with varying functionalities that will not affect the structure or inhibit material fabrication as reported in our previous work [36,37]. Thus, these proteins are useful candidates for designing mucoadhesive biopolymer systems because of their customizable physiochemical properties, where biocompatible SELP-based drug delivery systems that exploit favorable properties of mucosal membranes can be utilized.…”
Section: Introductionmentioning
confidence: 98%
“…Three HAP binding peptides, all of which were previously identified via phage display: CaP(S) STLPIPHEFSRE 8 – 11 , CaP(V) VTKHLNQISQSY 10 , 12 – 15 and CaP(H) SVSVGMKPSPRP 8 , 13 , 16 , 17 , have been used in this study. An extension of the approach to quantify the effect on mineralisation of larger proteins such as silk chimeras built from mimics of spider silk MASP1 protein and the CaP(V) peptide is also included 18 .…”
Section: Introductionmentioning
confidence: 99%